'It's your body, but…' Mixed messages in childbirth education: Findings from a hospital ethnography. (December 2017) - Newnham, Elizabeth; McKellar, Lois; Pincombe, Jan
Abstract: Objective: to investigate the personal, social, cultural and institutional influences on women making decisions about using epidural analgesia in labour. In this article we discuss the findings that describe practices around the gaining of consent for an epidural in labour, which we juxtapose with similar processes relating to use of water for labour and/or birth. Design: ethnography. Setting: tertiary hospital in Australian city. Participants: sequential interviews were conducted with 16 women; hospital staff (primarily midwives and doctors) participated during six months of participatory observation fieldwork. Findings: women were not given full disclosure of either practice and midwives tailored the information they gave according to the institutional policies rather than evidence. Key conclusions: informed consent is an oft-cited human right in health care, yet in maternity care the micro-politics of how informed consent is gained is difficult to ascertain, leading to a situation whereby the concept of informed consent is more robust than the reality of practice; an illusion of informed consent exists, yet information is often biased towards medicalised birth practices. Implications for practice: as primary maternity care-givers, midwives have a role in providing unbiased information to women; however it appears that hospital culture and policy affect the way that this information is presented. It is arguable whether women in such instances are giving true informed consent, and for this reason, the ethics of these hidden practices are questioned. Highlights: Risks of epidural analgesia are not fully disclosed to women Midwives tailor information given to women to conform with hospital policy It is questionable whether informed consent is achievable in these circumstances Midwives are ethically bound to provide evidence-based information Practice interactions can be used to uphold or resist biomedical discourse